Division of labor and collective functionality in Escherichia coli under acid stress - Sophie Brameyer; Kilian Schumacher; Sonja Kuppermann; Kirsten Jung (Communications Biology, 2022)
Using a triple fluorescent Escherichia coli reporter strain, cellular individuality in the activation of the three major acid-dependent amino acid decarboxylation systems under successively increasing acidic acid stress is quantitatively investigated. The observed heterogeneous activation of the systems indicates division of labor of the population to survive.